Evaluation of the in vitro antibacterial activity of essential oils of oregano and thyme against Ralstonia solanacearum - Rueda-Puente, Edgar Omar; Juvera Bracamontes, José Jesús; Romo López, Irma Gloria; Holguín Peña, Ramón Jaime (Revista Mexicana de Ciencias Agrícolas, 2018)
Ralstonia solanacearum (Rs), is a phytopathogenic bacterium of great importance worldwide known to cause the disease of bacterial wilt. This is a disease that devastates many crops, among them the potato. In order to find a natural alternative to control the Rs bacteria, the bactericidal power of the essential oils of oregano (Thymus vulgaris) and thyme (Lippia graveolens) was evaluated. The technique used for the analysis of the antibacterial activity was diffusion in agar, using sterile filter paper disks, 3 different dilutions were evaluated (1:1, 1:5 and 1:10) and 7.5, 10 and 15 μl were placed of each of the concentrations of the oils. The 70% alcohol was used in one of the filter paper discs as a negative control. In addition, a streptomycin (10 μg/disc) and ampicillin (10 μg/disc) were used as positive control. Dextrose agar medium and potato previously inoculated with the strain under study were used. After incubation, the halos of inhibition of bacterial growth were measured in millimeters. The analyzes were in triplicate. The essential oils of oregano and thyme showed inhibitory effects on the growth of Rs in the 1:1 dilution that turned out to be more effective than the rest of the dilutions evaluated, and the most effective amount applied was 15 μl of oregano essential oil and thyme compared the antibiotics used. Essential oils could be considered as an alternative for the control of Rs in plants.